The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1063/1.2219159
|View full text |Cite
|
Sign up to set email alerts
|

Explicit actions for electromagnetism with two gauge fields with only one electric and one magnetic physical field

Abstract: We extend the work of Mello et al. based on Cabbibo and Ferrari concerning the description of electromagnetism with two gauge fields from a variational principle, i.e., an action. We provide a systematic independent derivation of the allowed actions that have only one magnetic and one electric physical field and are invariant under the discrete symmetries P and T. We conclude that neither the Lagrangian, nor the Hamiltonian, are invariant under the electromagnetic duality rotations. This agrees with the weak-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…In addition it has recently been showed that, independently of boundary effects, a consistent definition of canonical structure is still possible [27]. To finalize let us stress that, independently of the above discussion, the canonical momenta π i A and π i C as defined in (13) are directly derived from the 3 + 1-dimensional theory, thus being consistent with the higher dimensional canonical momenta as derived in [19]. This is enough to justify the above choice.…”
Section: Electromagnetic Fields Canonical Momenta and Boundary Condisupporting
confidence: 54%
See 4 more Smart Citations
“…In addition it has recently been showed that, independently of boundary effects, a consistent definition of canonical structure is still possible [27]. To finalize let us stress that, independently of the above discussion, the canonical momenta π i A and π i C as defined in (13) are directly derived from the 3 + 1-dimensional theory, thus being consistent with the higher dimensional canonical momenta as derived in [19]. This is enough to justify the above choice.…”
Section: Electromagnetic Fields Canonical Momenta and Boundary Condisupporting
confidence: 54%
“…We note that the relations between the canonical conjugate momenta to Ai and Ci (13) and the electric and magnetic fields (12) hold a new correction due to the Chern-Simons boundary contribution in relation to the 3 + 1-dimensional relations obtained in [19]. Here we are referring to the last terms depending on k in the definitions of π i A and π i C in (13)).…”
Section: Electromagnetic Fields Canonical Momenta and Boundary Condimentioning
confidence: 99%
See 3 more Smart Citations